Serum Thyrotropin Is Positively Correlated with the Metabolic Syndrome Components of Obesity and Dyslipidemia in Chinese Adolescents - Jingfan Zhang; Ranhua Jiang; Ling Li; Ping Li; Xue Li; Zinan Wang; Liang Li; Weiping Teng (International Journal of Endocrinology)
Metabolic syndrome is a medical disorder characterized by obesity, hyperglycemia, dyslipidemia, and hypertension. Thyroid hormone has been shown to affect many metabolic processes. This study was undertaken to explore the relationship between serum thyrotropin and components of metabolic syndrome in Chinese adolescents. Waist circumference (76.4 ± 10.7 versus 70.0 ± 10.6 cm, P = 0.006) and body mass index (23.90 ± 4.20 versus 21.51 ± 4.16 kg/m2, P = 0.011) were significantly greater among adolescents with subclinical hypothyroidism compared with euthyroid subjects. The risk of obesity in the subclinical hypothyroid group was 3.444 times that in the euthyroid group (odds ratio = 3.444, 95% confidence interval (CI): 1.570–7.553). Serum TSH was significantly positively correlated with waist circumference (β = 1.512, P = 0.019), TC (β = 0.160, P = 0.003), LDL-C (β = 0.032, P = 0.008), and TG (β = 0.095, P = 0.001). The TSH level in the metabolic syndrome group was significantly higher than that in nonmetabolic syndrome group (2.65 [2.28–3.80] versus 2.53 [1.92–3.45] mIU/L, P = 0.032). Serum TSH within the reference range was positively associated with TC (β = 0.173, P = 0.013), LDL-C (β = 0.031, P = 0.043), and TG (β = 0.132, P = 0.021). Increased serum TSH in adolescents may be a potential risk factor for metabolic syndrome.